2017
DOI: 10.1038/s41598-017-00111-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatitis B core-related antigen is a satisfactory surrogate marker of intrahepatic covalently closed circular DNA in chronic hepatitis B

Abstract: Recently, hepatitis B core-related antigen (HBcrAg) has been suggested as an additional marker of hepatitis B virus (HBV) infection. This study aimed to investigate whether serum quantitative HBcrAg (qHBcrAg) was a satisfactory surrogate marker of intrahepatic covalently closed circular DNA (cccDNA). A total of 139 patients with liver biopsy were enrolled, consisting of 59 patients in immune tolerance (IT) phase, 52 patients in immune clearance (IC) phase, 18 patients in low-replication (LR) phase, and 10 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 17 publications
3
89
2
Order By: Relevance
“…The effectiveness of either serum HBcrAg or HBsAg in reflecting intrahepatic cccDNA level had been identified in cohorts of patients with different races and viral genotypes . Though a positive correlation was reported between HBcrAg and HBsAg in HBeAg‐positive patients without antiviral therapy, the intensity of correlation was moderate ( r = 0.564), which indicated that serum HBcrAg and HBsAg could not replace each other . Additionally, serum HBcrAg and HBsAg had unique patterns of distribution throughout the five disease phases of CHB, including high detectability rates of serum HBcrAg after HBsAg seroclearance, which decided the different possibilities for their applicability in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of either serum HBcrAg or HBsAg in reflecting intrahepatic cccDNA level had been identified in cohorts of patients with different races and viral genotypes . Though a positive correlation was reported between HBcrAg and HBsAg in HBeAg‐positive patients without antiviral therapy, the intensity of correlation was moderate ( r = 0.564), which indicated that serum HBcrAg and HBsAg could not replace each other . Additionally, serum HBcrAg and HBsAg had unique patterns of distribution throughout the five disease phases of CHB, including high detectability rates of serum HBcrAg after HBsAg seroclearance, which decided the different possibilities for their applicability in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many noninvasive convenient markers have been investigated to reflect intrahepatic cccDNA level . As a classic indicator, serum hepatitis B surface antigen (HBsAg) levels have long been thought to be correlated with intrahepatic cccDNA, but this correlation is not strong …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBcrAg consists of HBcAg, HBeAg and p22cr, the precore protein. Promising new data show that qHBcrAg is a reliable marker of viral replication and a good surrogate of intrahepatic HBV cccDNA . Further, different levels of qHBcrAg reflect distinct phases of infection, predict the CHB clinical complications and guide antiviral therapy management …”
Section: Introductionmentioning
confidence: 99%
“…It is now recognized that factors other than the quantity of cccDNA in infected hepatocytes, its transcriptional regulation, and the possibility that envelope proteins could be expressed from viral sequences integrated into the host genome also contribute to HBsAg levels . As HBcrAg may correlate with serum HBV DNA and intrahepatic cccDNA, as shown in patients treated with NA with a decline in intrahepatic cccDNA, it is possible that HBcrAg may better reflect the intrahepatic compartment than HBsAg …”
Section: Viral and Immune Aspects Of Therapymentioning
confidence: 99%